Case Studies of Building Pathology in Cultural Heritage - Delgado, João M.P.Q.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book highlights new developments in the field of building pathology and rehabilitation, taking an in-depth look into current approaches to the surveying of buildings and the study of defect diagnosis, prognosis and remediation. Including a number of real-world case studies and a detailed set of references for further reading, the book will appeal to a wide readership of scientists, practitioners, students and lecturers.
Survey and identification of pathological manifestations in Olympic Stadium of Cascavel city -- Pathology Analysis and Intervention at the "Pavilhão Mourisco" Roof Terraces - Rio de Janeiro, Brazil -- Finding faults in residential buildings -- Experience from Using Prefabricated Elements for Adding Insulation and Upgrading of External Façades -- Recovery and enhancement of modern architectures: the case of cinema Ariston in Potenza (Italy) -- Plumbing system´s pathologies based on the record of technical assistance and design procedures -- Cracks of masonry partition walls in multifloor building: case study -- Survey and dynamic behaviour of the Our Lady of Conception Church, Portugal -- Building refurbishment - economical relevance of the several construction elements -- Analysis of the microclimate in a historical building to assess the probability of recurrence of filamentous fungi -- Maintenance as a tool to avoid building pathology. The Oporto building example -- An interoperable ICT tool for asset and maintenance management - Advances in research -- BIM methodology used in the maintenance of buildings.
Keywords: Building materials; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Cultural property; Building Materials; Structural Materials; Engineering Thermodynamics, Heat and Mass Transfer; Cultural Heritage